Classifying computer-mediated communication (CMC) interruptions at work using control as a key delineator. Issue 2 (25th January 2021) - Russell, Emma; Jackson, Thomas; Banks, Adrian
ABSTRACT: Computer-mediated communication (CMC) interruptions are a common feature of people's work activity. In studying interruptions, researchers can understand how people manage and co-ordinate their work when faced with multiple, often competing, demands. However, CMC interruptions are characteristically different from each other and impact people's work performance in different ways. In this theoretical paper, we define and differentiate between computer-mediated communication (CMC) interruptions, according to the level of control people are able to exert over an interruption at different points in the delivery timeline. Informed by the extant interruptions literature and Action Regulation Theory, a classification framework is provided, to help researchers and work designers distinguish which types of real-world CMC interruption are more or less disruptive, based on levels of control. Using the developed framework, two key research propositions are made, which we encourage future research to attend to. Unique contributions and implications of this paper are discussed.